Exploring Pedagogical Practices in Mathematics Education - Onesme Niyibizi; Marie Claudine Uwitatse; John Peter Kazinyirako; Thierry Niyitegeka; Vedaste Mutarutinya (Journal of Research in Education and Pedagogy, 2025)
This study aimed to investigate effective teaching strategies in mathematics education through a multi-method qualitative approach. Data were collected from two purposefully selected secondary schools, involving classroom observations, interviews with two mathematics teachers, and document analysis. The research sought to provide a comprehensive understanding of the teachers’ instructional methods, drawing on various data sources to explore how these methods influence student learning and engagement. In-depth interviews with the teachers provided rich insights into their beliefs, experiences, and motivations regarding mathematics education. These interviews allowed the teachers to reflect on the challenges they face, the factors shaping their teaching practices, and their strategies for engaging students. Classroom observations captured the day-to-day dynamics of teaching, offering a real-time view of how the teachers applied pedagogical techniques, managed classrooms, and interacted with students, while also highlighting the level of student participation and attention. Additionally, the study analyzed instructional materials, lesson plans, and assessments to assess how well the teachers’ practices aligned with curriculum objectives and educational standards. The findings revealed different approaches to mathematics instruction, revealing both the strengths and limitations of the methods employed. This research contributes to the growing body of knowledge on mathematics pedagogy in public secondary schools, offering valuable insights for future improvements and further research into enhancing teaching practices in the classroom.